Comparison of external calibration and isotope dilution methods for iodine determination in foods by inductively coupled plasma mass spectrometry - Juntima Photi; Premmin Srisakda; Tiyanun Jurkvon; Christophe Zeder; Kunchit Judprasong (Food Chemistry: X)
This study sought to validate the external calibration curve (CAL) method for iodine analysis in 26 selected foods and then to compare the test result with the isotope dilution mass spectrometry (IDMS). Iodine was extracted by tetramethylammonium hydroxide (TMAH) and determined by ICP-MS using CAL and IDMS methods. The results showed that iodine determination using the IDMS method had higher precision than the CAL method (LOD of the method were 0.01 and 0.02 mg/kg, respectively). However, both methods showed good accuracy and precision for all SRM and the 26 food samples. Test results from both methods had a strong correlation (R2 > 0.998) and no significant difference between the determination methods, even within test sample sectors based on the distribution in the AOAC food triangle (p > 0.970). 129I spiked into the sample before or during alkaline extraction showed no significant difference in the test results (p = 0.989).